Enjeu des droits fonciers dans la gestion des ressources naturelles - Caroline Plançon (VertigO)
This paper underlines that the individual, absolute ownership is not the only possible way to productive use of land and natural resources, it means that the land title is not the only possible manner to put the land in use, despite of the main stream of thinking.For this purpose, it is useful to specify some legal categories and concepts, such as the governance, its link with the right/law, and to present how legal anthropology can bring to the environmental questions in situations of legal pluralism, in particular by underlining that this methodology takes into account the various legal cultures to the natural resources management, in particular by focusing that lands and natural resources are not always considered with a commercial and financial point of view. In the second time, the text details how the land question, is in the middle of the natural resources management, in particular with regard to the property rights. But, “about which properties rights does one speak?” What does it recover in terms of rights but also of duties of protection, as well of the resources as the populations which live about it? A diving in the structure of the “various dismembered rights of property” makes it possible to consider the access to the land and the natural resources from the bond of obligation and responsibility in the various uses related to the territory.